Antimicrobial and antioxidant activity of bacterial endophytes isolated from leaves of the mangrove plant Rhizophora stylosa - Dat, Ton That Huu; Oanh, Phung Thi Thuy; Tam, Vu Thi Thanh; Anh, Hoang Le Tuan (Academia Journal of Biology, 2019)
Mangroves are the most productive ecosystems and contain highly diverse plants and microbial communities. Mangrove endophytes are proved to be a rich source of bioactive secondary metabolites. The biological molecules produced by endophytes play an important role in protection of mangrove plants against herbivores, insects as well as pathogens. The present study aimed to isolate the endophytic bacteria from the mangrove plant Rhizophora stylosa and screen antimicrobial and antioxidant activity of ethyl acetate extracts from the isolated endophytic bacteria. A total of 64 endophytic bacterial strains from R. stylosa leaves were isolated, of which ethyl acetate extracts of 14 isolated endophytic strains showed antimicrobial activity against at least one of reference microorganisms Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 25923, Bacillus subtilis ATCC 27212, Staphylococcus aureus ATCC 12222 and Candida albicans ATCC 7754 with MIC values from 32 to 512 µg/ml. Among them, four strains showed activity against one reference microorganism, five strains showed activity against two reference microorganisms, four strains showed activity against three reference microorganisms, and one strain showed activity against four reference microorganisms. Additionally, the ethyl acetate extracts of 12 isolated endophytic bacteria showed ATBS and DPPH radical scavenging activity with scavenging values from 36.27 ± 2.6% to 71.46 ± 6.6% and from 26.22 ± 3.3% to 57.38 ± 5.8%, respectively. The identification of the five most active endophytic bacteria by 16S rRNA sequences revealed that the endophytes belonged to four genera, including Bacillus, Streptomyces, Pseudovibrio and Pseudomonas. The obtained results suggest that the endophytic bacteria from mangrove plants are a promising reservoir of antimicrobial and antioxidant agents.